Analysis of Locutionary, Illocutionary and Perlocutionary Speech Acts in Product Advertisements on Television - Syaidah Islami; Intan Sari Ramdhani (CV. Rayyan Dwi Bharata, 2023)
This speech act research aims to examine the language used in product advertisements on television. In this study, researchers used a qualitative approach and used descriptive methods. The descriptive method is used to describe the types of speech acts in product advertisements on television. The subject of this study is the product that will be shown on television, while the research object is the speech act in a product advertisement on television. Data collection techniques in this study used recording, observing, and note-taking techniques. Based on the method used, the research results obtained in the form of locutionary, illocutionary, and perlocutionary speech acts in product advertisements on television. The conclusion from the researcher is that the declarative form of locutionary speech acts in the Superstar Snaps advertisement, the illocutionary function in the form of the commissive function of the sentence form